2018
DOI: 10.1051/matecconf/201816205005
|View full text |Cite
|
Sign up to set email alerts
|

Assessment study of water quality index (WQI) for Shatt Al-arab River and its branches, Iraq

Abstract: Shatt Al-Arab River (in Basrah province South of Iraq) is approximately 192 km long. It plays a key role in providing water for domestic purposes, irrigation, manufacturing, in addition to shipment. Recently the river suffers from increasing pollution, due to wastes from industries, domestic sewage and agricultural activities that find their way into water sources and result in large scale deterioration of water quality. Investigating the river size and significance, becomes necessary to perform a study to und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…The water quality is divided into five classes (Table: S2) and considered very bad (0–25), bad (26–50), medium (51–70), good (71–90), and excellent (91–100) (Hamdan et al 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…The water quality is divided into five classes (Table: S2) and considered very bad (0–25), bad (26–50), medium (51–70), good (71–90), and excellent (91–100) (Hamdan et al 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…The concentrations of TDS and Turbidity, greatly increase in the downstream direction (Table 1). The reported of mean values for TDS concentrations which include those acquired in other studies of the Shatt Al-Arab River basins in the study area, as reported by [23,41]. The mean values of the Alkalinity (Alk) (154.04 ppm) were actually above the WHO limits (up to 10 ppm) as shown in Table 1.…”
Section: Resultsmentioning
confidence: 54%
“…Water quality was found to be poor towards the governorate's center, along the river forks. Furthermore, it was determined that high sewage water discharged into the river, particularly river branches, as well as illegal industrial effluent and sewage discharges, were the primary causes of river pollution [13]. WQI and GIS software were used to water quality assessment along Tigris River in Iraq.…”
Section: Introductionmentioning
confidence: 99%